Computation of the floating dock k-n curves by the calculation of buoyancy center coordinates - ناصيف , بشرى; حوا, رامي; هيثم عيسى (Latakia University Journal -Engineering Sciences Series, 2023)
This paper presents a new equations enables to calculate the floating Docks buoyancy center coordinates. The k-n value is directly calculated as a function of buoyancy center coordinates. the floating dock is a structure that can be submerged to allow the ship to enter and dock, and then raise it to raise the ship from the water for repair or maintenance. The floating dock system is a simple way to lift ships to speed up maintenance and repair The buoyancy center of the dock is calculated for a fixed value of the heel angle, and by scanning over a successive displacement values. As we scan for different values of displacement many cases of the dock geometry had been distinguished. For each case we calculate the displacement and the buoyancy center coordinates. In this paper, we developed a very accurate floating Docks equilibrium calculation as a result of our formulation of precise mathematical equations, and we did not use numerical integrals. The results obtained are essential and indispensable during the assessment of the equilibrium of the floating basin, especially in emergency situations